An insight into the use of personality assessment by U.K. sport psychology consultants - Rowles, S.; Holder, T. (The Sport Psychologist, 2023)
Personality has a long, if somewhat checkered history in the sport psychology literature, but insight into its use in contemporary applied practice is more limited. This study investigated contemporary sport psychology consultants` perceptions of using personality assessment. Ten participants (four female and six male; mean 14 years` applied experience), all Health and Care Professions Council-registered and accredited by either the British Psychological Society or British Association of Sport and Exercise Sciences, were purposefully sampled and interviewed. An inductive thematic analysis was then performed. Five themes were identified: effective practice, perceived impact, societal movements, organizational experience, and innovation. Findings deliver an original insight into the perceptions of practitioners around personality assessment in sport, illustrating a movement from prediction to development in the field and providing novel examples of bespoke, individualized tool application. Broad training and career experiences will help practitioners fully appreciate these potential opportunities.